Deteksi Golongan Senyawa Ekstrak Kasar Metabolit Ekstrasel Mikroalga Laut Spirulina sp. Sebagai Agen Antioksidan - Anggraini, Yulistia; Winahyu, Diah Astika (Journal of Science and Applicative Technology; Vol 5 No 1 (2021): Journal of Science and Applicative Technology June Chapter, 2021)
Microalgae excrete antioxidant compounds as a defense system to protect themselves from the danger of ultraviolet rays. These compounds also can be used as the organic materials of cosmetics or medicines. This study aimed to determine the antioxidant activity of marine microalgal extracellular metabolite extract of Spirulina sp.. Extracellular metabolites were extracted from the residual media filtrate from the harvesting. The qualitative antioxidant test’s results using the thin-layer chromatography technique and 2,2-diphenylpycrilhydrazil (DPPH) reagent showed antioxidant activity. Moreover, the component identification using ninhydrin and Dragendorff reagent in thin layer chromatography test showed alkaloid and peptide compounds. To support the results, the identification using infrared spectrum analysis showed the peaks at 1117 cm -1 (C-N and C-C stretching), 1458 cm -1 (C-H bending of methyl group), 1635 cm -1 (C=O stretching of amide group), and 3454 cm -1 (N-H stretching of amine and amide groups).